A fuzzy-set analysis of hard and soft sciences publication performance - Curado, Carla (2022)
This paper examines the differences between the publication performance (PP) of the scientific research areas (SRAs) of the hard and soft sciences. Intrigued by the significant statistical difference between the average publication levels of researchers fromthe hard and soft SRAs, this paper addresses the factors influencing researchers' publication levels. The study uses an online survey to gather data from 663 researchers from 140 research centers. A comparison of the parsimony solutions for the hard and soft sciences shows only two common pathways, thus providing evidence of different sufficient condition sets for publication for the two SRAs. The global intermediate solutions account for over 85% of the study's outcome variable, with consistency levels of more than 75%. The results show differences in the sufficient condition sets for the two SRAs that may be attributed to the variations in their scientific conceptual frameworks and the research methods applied by each discipline. Notably, having tenure seems to make a difference.